Democratic Advisory Committee Minutes of Foreign Policy Task Force (1967)
Minutes record the third meeting of the Democratic Advisory Committee's Foreign Policy Task Force at the Ambassador Hotel in Los Angeles, listing extensive attendance. The meeting focused on controversy over premature publicity of the Vietnam and Far East Subcommittee report, resulting in a motion to incorporate its work into a broader foreign policy report and to include alternative Vietnam statements reflecting dissenting views. Leadership and organizational steps were taken, including appointing co-chairs, assigning study areas modeled on Blueprint for Peace, and directing preparation of alternate Vietnam position statements. Members also discussed plans for presenting task force policy statements at the upcoming Fresno Conference in January, where they would serve as the basis for seminar discussions rather than formal votes. The session concluded with logistical considerations to ensure adequate time and attention for the Foreign Policy seminar at the conference.